2004
DOI: 10.1037/0278-7393.30.5.969
|View full text |Cite
|
Sign up to set email alerts
|

Three Turtles in Danger: Spontaneous Construction of Causally Relevant Spatial Situation Models.

Abstract: In 4 experiments, the author explored the spontaneous construction of spatial situation models during discourse comprehension by using the sentence-recognition paradigm of J. D. Bransford, J. R. Barclay, and J. J. Franks (1972). In Experiment 1, signaling causal relevance of spatial relations was a necessary precondition for replicating their original finding of spontaneously constructed spatial representations. Causal relevance was ensured in the subsequent experiments by a judgment task indirectly demanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 77 publications
(157 reference statements)
1
19
0
1
Order By: Relevance
“…However, results of our study as well as recent research suggest that readers focus on dimensional shifts that are causal relevant. Jahn (2004) reported that causal relevance is a precondition for the spontaneous construction of situation models, and Sundermeier et al (2005) showed that speeded recognition is improved when probe words are causally relevant. In general, inference generation are cognitively demanding processes (e.g., Britton and Graesser 1996;Friedman and Miyake 2000;Kintsch 1998).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, results of our study as well as recent research suggest that readers focus on dimensional shifts that are causal relevant. Jahn (2004) reported that causal relevance is a precondition for the spontaneous construction of situation models, and Sundermeier et al (2005) showed that speeded recognition is improved when probe words are causally relevant. In general, inference generation are cognitively demanding processes (e.g., Britton and Graesser 1996;Friedman and Miyake 2000;Kintsch 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Participants' response times to a probe word were smaller when the probe was causally relevant than when it was not. Also for the spontaneous construction of spatial situation models causal relevance is an important precondition (Jahn 2004). Overall, numerous studies indicate that understanding causal relations does indeed take a prominent role in narrative understanding (e.g., Brownstein and Read 2007;Poynor and Morris 2003;Sundermeier et al 2005;Trabasso 1989;Trabasso and Sperry 1985;Trabasso et al 1995;Trabasso and van den Broek 1985;van den Broek and Trabasso 1986;Wolfe et al 2005) and they suggest that readers might primarily focus on causal relations above all other situation model dimensions.…”
mentioning
confidence: 96%
“…Much recent work suggests that spatial information may only be tracked in the context of relevant cues such as reading goals, temporal shifts, and causal relatedness (e.g, de Vega, 1995;Jahn, 2004;Levine & Klin, 2001;Magliano, Miller, & Zwaan, 2001Morrow, Greenspan, & Bower, 1987;Rapp & Taylor, 2004;Rich & Taylor, 2000;. Thus, mental models containing comprehensive spatial information may only develop under very limited circumstances.…”
Section: Developing Spatial Mental Modelsmentioning
confidence: 98%
“…For example, when people read sentences that described an event, causal relevance was a necessary condition for them to spontaneously generate spatial models of that event (Jahn, 2004). People also monitor model dimensions and the ways they interact to aid their comprehension.…”
Section: Situation Model Updating and Expectationmentioning
confidence: 99%